Cell attachment study of chicken fibroblast cell(DF-1) using ceramic microcarrier granule in bioreactors - Mel, Maizirwan; Sopyan, Iis; Ahmad Nor, Yusilawati (Malaysian Medical Association, 2008)
Tricalcium phosphate ceramic microcarrier has been developed and introduced to a new possibility for the culture of anchorage dependent animal cells of DF1. It was observed that the number of attached cells was increased with shorter time for both spinner vessel and stirred tank CST) bioreactor. For those bioreactors, the total viable cell number that had been obtained is about 1.2 x 10' celi/mi.